Figure of Speech in Novel of Mice and Men and Seek The Translation Quality from Two Different Gender Translator Version: What is the influenced factor? - Lailatun Najakh; Mangatur Rudolf Nababan; Djatmika Djatmika (Yayasan Visi Intan Permata, 2018)
The analysis of novel cannot be drawn away from its figures of speech. Figures of speech every author is different and that beauty of writing attracts reader’s interest. The following issue is about how this literary work can arrive closely to its original version when it is translated by two different gender of translator. Besides, translator may bring their own ideological gender background. Regarding to this issue, obviously, the quality of target text version is in a huge questioning. Further, this research used novel Of Mice and Men by John Steinbeck and pays attention to find out figure of speech found in novel Of Mice and Men, the translation techniques choose in that novel, and the impact of translation techniques to translation quality from two different gender translators. The research method of this research was descriptive qualitative with collecting data, validating data, and analyzing data in order to get result. The source of data were novel Of Mice and Men (Tikus dan Manusia) translated by Pramoedya Ananta Toer and Ariyantri E. Tarman. Data collection was using purposive sampling. This result showed that there were eight figures of speech found in novel Of Mice and Men. In terms of their translation techniques, the most applied techniques by female translators were established equivalent and male translators were also established equivalent followed by creative discursive. In addition, the chosen techniques by female translator gave higher accuracy than male translator. Meanwhile the acceptability and readability were high from both translators. However, the result didn’t find any correlation between gender ideology and the chosen techniques. The chosen techniques were more likely influenced by the translator job background. The background of male translator as the famous novelist gave his strong ideology also transferred to his work as translator. Meanwhile, the female translator worked faithfully to source text.